Analysis of Organizational Strengthening Dimensions in Institutional Capacity Building of the Aceh Ulama Consultative Assembly - Taufik,; Ramadani, Anggi (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This study aims to analyze the dimensions of organizational strengthening at the Aceh Ulama Consultative Assembly (MPU) institution. This research uses a descriptive qualitative approach with data collection techniques in the form of interviews through open-ended questions. Field observations were made in the form of observations on organizational work culture, employee empowerment, and other activities at the Secretariat of the Aceh MPU Institution. Secondary data was reviewed on documents relevant to the research, such as performance reports, financial reports, regulations relating to MPU Aceh. The results of the study found that the organizational strengthening dimension of the Aceh MPU Institution in the aspect of the incentive system has been running well, there is an incentive system obtained by MPU Aceh members according to applicable regulations. The leadership aspect cannot be categorized as collective or network leadership. The coordination of MPU Aceh so far has only been internal to the organization between the Provincial MPU and the district / city MPU. It has not yet carried out cross-agency coordination. Collaborative leadership is the art of leading by involving many actors/institutions in the problem-solving process. This leadership model is very helpful in overcoming the limitations experienced by MPU Aceh in carrying out its duties and functions. In the aspect of employee empowerment, it has been running well, there is a division of labor through existing commissions. Organizational strengthening at MPU Aceh, which includes components of the incentive system, employee empowerment, leadership, organizational culture, and communication, will be more optimal if supported by strong and collaborative leadership.